2000
DOI: 10.1177/0165551004232970
|View full text |Cite
|
Sign up to set email alerts
|

Visualization in information retrieval: a three-level analysis

Abstract: Visualization in information retrieval (IR) is a rapidly emerging area in which human-computer interaction (HCI)is adapted to the design of interfaces for IR systems. There are numerous proposals for the development of new visual IR systems. In parallel with the advent of advanced software and hardware, the attempts to design visualization-based IR systems are stimulated with the promise that information visualization applies visual processing to abstract information. Under this rapid development in the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…However, as information is rapidly growing in quantity, heterogeneity and dimensionality, designing such systems has become an increasingly difficult task (Gerken et al, 2009). As the interaction between users and visual representations takes place during information seeking, a poor representation could not only burden users more but also disturb their information-seeking process (Song, 2000).…”
Section: Visual Information Retrieval Systemsmentioning
confidence: 99%
“…However, as information is rapidly growing in quantity, heterogeneity and dimensionality, designing such systems has become an increasingly difficult task (Gerken et al, 2009). As the interaction between users and visual representations takes place during information seeking, a poor representation could not only burden users more but also disturb their information-seeking process (Song, 2000).…”
Section: Visual Information Retrieval Systemsmentioning
confidence: 99%
“…Historically, cartographers have designed maps to fulfil this function; in a digital environment geovizualization has been developed to promote the exploration of GI [35]. This activity is developing in parallel with work on visualization in information retrieval [36].…”
Section: Exploration Levelmentioning
confidence: 99%
“…Song [11], in an article with 120 references, shows that there is no shortage of activity in this field. If visualisation is to become widely adopted for information retrieval, as Song says, '[it] must be preceded by both knowledge of textual analysis and data conversion and it has been identified that the decision in choosing a visualization technique must be made on the basis of understanding data types and data representations.…”
Section: Visualisation Describedmentioning
confidence: 99%